2022
DOI: 10.3389/fimmu.2022.1045624
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived extracellular vesicles modulate innate immune responses to affect tumor progression

Abstract: Immune cells are capable of influencing tumor progression in the tumor microenvironment (TME). Meanwhile, one mechanism by which tumor modulate immune cells function is through extracellular vesicles (EVs), which are cell-derived extracellular membrane vesicles. EVs can act as mediators of intercellular communication and can deliver nucleic acids, proteins, lipids, and other signaling molecules between cells. In recent years, studies have found that EVs play a crucial role in the communication between tumor ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 193 publications
0
7
0
Order By: Relevance
“…Macrophages, which are present in various parts of the body, perform crucial functions by regulating the immune system, inflammatory responses, antigen presentation, angiogenesis, and remodeling [ 36 ]. The tumor microenvironment (TME) is enriched with tumor-associated macrophages (TAM), which are key drivers of tumor progression, metastasis, and therapeutic resistance [ 37 ].…”
Section: Biogenesis and Sourcementioning
confidence: 99%
“…Macrophages, which are present in various parts of the body, perform crucial functions by regulating the immune system, inflammatory responses, antigen presentation, angiogenesis, and remodeling [ 36 ]. The tumor microenvironment (TME) is enriched with tumor-associated macrophages (TAM), which are key drivers of tumor progression, metastasis, and therapeutic resistance [ 37 ].…”
Section: Biogenesis and Sourcementioning
confidence: 99%
“…EVs derived from tumors can modulate the immune responses of the host through a range of pathways, which includes promoting pro-inflammatory effects ( Wang et al, 2022 ). Tumor-derived EVs induce monocytes to release pro-inflammatory cytokines.…”
Section: Immune Cells and Tumor Cell-derived Evs Act As Modulators Of...mentioning
confidence: 99%
“…For immune cells and tumor vesicles, it was demonstrated that EVs can both stimulate and inhibit lymphocytes depending on ratio and membrane composition. Effects of tumor EVs on immune cells were recently reviewed in ( Ukrainskaya et al, 2019 ; Wang et al, 2022 ) Below we will discuss the role of EVs produced by glioma/glioblastoma in establishment of immune suppressive microenvironment.…”
Section: Extracellular Vesicles Transfer Information Between Cellsmentioning
confidence: 99%